GABA signalling in human pancreatic islets - Jin, Zhe; Korol, Sergiy V. (Frontiers in Endocrinology, 2023)
The pancreatic islets are essential microorgans controlling the glucose level in the blood. The islets consist of different cell types which communicate with each other by means of auto- and paracrine interactions. One of the communication molecules produced by and released within the islets is γ-aminobutyric acid (GABA), a well-known inhibitor of neuronal excitability in the mammalian nervous system. Interestingly, GABA is also present in the blood in the nanomolar concentration range. Thus, GABA can affect not only islet function per se (e.g. hormone secretion) but also interactions between immune cells and the pancreatic islet cells in physiological conditions and in pathological states (particularly in type 1 diabetes). In the last decade the interest in GABA signalling in islets has increased. The broad research scope ranges from fundamental physiological studies at the molecular and cellular level to pathological implications and clinical trials. The aim of this mini-review is to outline the current status of the islet GABA field mostly in relation to human islets, to identify the gaps in the current knowledge and what clinical implications GABA signalling may have in islets.